Economic dispatch of power system containing UHVDC with direct power purchase by large consumers. Issue 16 (9th January 2019) - Qian, Hanhan; Jiang, Yitian; Xiang, Wei; Li, Yongbo; Hua, Yuting; Lin, Zhemin; Wang, Kai
Abstract : With the integration of the ultra‐high‐voltage direct‐current (UHVDC) of large capacity, the scheduled outputs of the power plants are limited, and the direct power purchase (DPP) by large consumers is influenced. The negative impact caused by the failure modes of the UHVDC on the economic dispatch (ED) and the security of the power system is to be studied. Here, the derated capacities of the UHVDC are described together with their state probabilities. To maximise the profit of power plants, an ED model with the DPP is proposed. The relationship between the amount of the DPP and the power transmission by the UHVDC is decided based on two contract strategies for the DPP. The interior‐point method is applied to solve the ED problem. The simulation results validate the feasibility and accuracy of the proposed model, which is beneficial to the development of the power market and the UHVDC in China.